Playing in the sandbox: state building in the space of non-recognition. - Richards, Rebecca; Smith, Robert (Third World Quarterly, 2015)
For unrecognised states in the international system recognition of sovereign statehood is the ultimate goal. Not being ‘a state’ means being excluded from global networks. However, even in the most basic definitions and criteria for unrecognised states there is a period of relative autonomy accorded due to non-recognition. This is a period when political actors can use isolation to establish the state’s narrative, identity and structure. It is this period that provides the foundations for external interaction. It is in this period that the state is born. This article examines another side to the politics of recognition: the politics of non-recognition. Drawing on the contemporary examples of Somaliland and Kurdistan, the article assesses the benefits as well as the costs of non-recognition.